Map of Enviromental Road Conditions in Lereng Village Kuok District Using GIS - Agus, Muhammad; Setiawan, Beny; Alisa Putra, Agus (Journal of Engineering Science and Technology Management, 2025)
Roads are land transportation infrastructure that includes all parts of the road system, such as connecting structures, complementary buildings, and equipment intended for traffic activities on, above, and below the ground surface, including water surfaces, excluding railways, haul roads, and cable roads. This research aims to identify the condition of environmental roads in Lereng Village, Kuok District, and to produce a spatial distribution map of the environmental road network. The study applies a survey-based quantitative descriptive method, focusing on describing actual conditions and revealing factual problems found in the field. Primary data were obtained through direct field observations and measurements, while secondary data were collected from related institutions. Geographic Information Systems were selected as the main analytical tool due to their ability to manage spatially referenced data, process complex structures, and efficiently support decision making related to road infrastructure management. The results show that most environmental roads in Lereng Village are in damaged condition, dominated by potholes, longitudinal cracks, and surface deterioration. Several roads are classified as heavily damaged, including Transad Alley 1, Transad Road 2, and other local roads within the village area. These conditions reduce driving comfort and safety for road users and indicate the urgent need for improvement. The mapping results produce an environmental road condition map with priority scores ranging from 9 to 18. Roads with priority values greater than 7 are categorized as requiring routine maintenance, providing a basis for planning maintenance and rehabilitation programs.